Antibiogram and Minimum Inhibitory Concentration of Selected Antibiotics against Vibrio cholerae Isolated from Sewage Samples (Tribhuvan University Journal of Microbiology, 2025)
Objectives: The purpose of this study was to perform antibiogram profiling and determine minimum inhibitory concentration (MIC) of selected antibiotics against Vibrio cholerae isolated from sewage samples.Methods: A cross-sectional study was carried out at the microbiology and molecular biology laboratory of Central Campus of Technology. A total of 45 sewage samples were collected. The samples for this study was aseptically collected from different places of Sunsari district of Eastern Nepal and subjected to isolation and identification of V. cholerae., followed by antibiotic susceptibility testing by Kirby Bauer disc diffusion method. MIC was performed by selecting three antibiotics ampicillin, tetracycline and streptomycin and was done by microtiter plate method.Results: A total of 24 V. cholerae (53.33%) were isolated. From the total samples, 53.33% (n=13) were found to be resistant against Erythromycin and Tetracycline. 66.67% (n=16) samples showed that the bacterium was resistant to cefotaxime. 93.33% (n=22;) samples were sensitive to ciprofloxacin where as 66.67% (n=16) samples were sensitive to ampicillin and cotrimoxazole. 14 isolates were inhibited by Ampicillin at concentrations below 8 μg/ml, while 8 and 10 isolates were inhibited by Tetracycline and Streptomycin, respectively at concentrations below 4 μg/ml.Conclusions: This sewage-based V. cholerae antibiogram study underscores sewage as a reservoir and urges sewage control. ampicillin, erythromycin, and tetracycline show limited efficacy, in contrast to ciprofloxacin, ampicillin, and cotrimoxazole, which remain viable for treating much of cholera.